2013
DOI: 10.21149/spm.v55s1.5097
|View full text |Cite
|
Sign up to set email alerts
|

Infecciones de transmisión sexual. Perfil de atención en zonas fronterizas de Centroamérica (2007-2010)

Abstract: Objetivo. Analizar el perfil de atención por infecciones de transmisión sexual (ITS) en centros de salud de zonas fronterizas de Centroamérica durante el periodo 2007-2010. Material y métodos. Estudio transversal en una muestra de 3 357 pacientes. Se capacitaron médicos y se suministraron medicamentos, condones y pruebas de VIH (paquete básico de atención [PBA]). Se analizaron las características sociodemográficas de los participantes y su asociación a la recepción del PBA. Resultados. De la muestra, 66.0% tuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“… ID Reference Method Location Population Objective 1 Acharya (2010) Qualitative Mexico 60 female internally trafficked sex workers, exact age range unspecified but below age 18 to over age 24 Extreme violence and health risks of victims of sex trafficking 2 Camarena Ojinaga et al. (2017) Qualitative Mexico northern border 60 indigenous female internal migrants aged 17–60, 4 key informants from medical staff Indigenous migrant women's experiences with health services and their understanding of their sexual and reproductive rights 3 Serván-Mori et al. (2013) Quantitative Central America and Mexico 3128 females aged 10–60+ presenting to clinics with sexually transmitted infections, includes internal and international migrants Analyze the profile of care for sexually transmitted infections (STIs) in health centers in border areas 4 Medecins Sans Frontieres (2017) Mixed methods Mexico 56 women of 467 total participants, mostly Central American migrants in migrant shelters, exact age range unspecified but less than 18 to over 35 years Measure exposure to violence and impact on health, barriers to health care, and limited access to protection of migrants 5 Goldenberg et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… ID Reference Method Location Population Objective 1 Acharya (2010) Qualitative Mexico 60 female internally trafficked sex workers, exact age range unspecified but below age 18 to over age 24 Extreme violence and health risks of victims of sex trafficking 2 Camarena Ojinaga et al. (2017) Qualitative Mexico northern border 60 indigenous female internal migrants aged 17–60, 4 key informants from medical staff Indigenous migrant women's experiences with health services and their understanding of their sexual and reproductive rights 3 Serván-Mori et al. (2013) Quantitative Central America and Mexico 3128 females aged 10–60+ presenting to clinics with sexually transmitted infections, includes internal and international migrants Analyze the profile of care for sexually transmitted infections (STIs) in health centers in border areas 4 Medecins Sans Frontieres (2017) Mixed methods Mexico 56 women of 467 total participants, mostly Central American migrants in migrant shelters, exact age range unspecified but less than 18 to over 35 years Measure exposure to violence and impact on health, barriers to health care, and limited access to protection of migrants 5 Goldenberg et al.…”
Section: Resultsmentioning
confidence: 99%
“…Only one paper also mentioned issues possibly indicative of psychosexual dysfunction and another mentioned cancers ( Acharya, 2010 ; Camarena Ojinaga et al., 2017 ), while 9 studies included mental and emotional health ( Medecins Sans Frontieres, 2017 ; Morris et al., 2013 ; Rodriguez-Montejano et al., 2015 ; Goldenberg et al., 2018 ; Medecins Sans Frontieres, 2020 ; Cardenas-Rodriguez and Vázquez Delgado, 2014 ; Acharya, 2019 ; Stephen, 2019 ; Wang et al., 2019 ). To be more specific, the study of risk factors, prevention interventions and detection of prevalence of sexually transmitted infections (often HIV) dominated, with only rare mention of other genitourinary problems such as urinary tract infections, abnormal vaginal discharge and other issues of gynecological illness and pain ( Acharya, 2010 ; Serván-Mori et al., 2013 ; Medecins Sans Frontieres, 2017 ). The mention of cancers was in a study of internal migrants in Mexico who confirmed that they knew about and undertook screening for cervical and breast cancer ( Camarena Ojinaga et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Se han observado las experiencias y derechos sexuales de centroamericanos en tránsito a los Estados Unidos (9). Se detallan cuestiones sobre el perfil de atención por infecciones de transmisión sexual de zonas fronterizas de Centroamérica (10); o bien se esclarece el panorama sobre la tasa de uso del condón relacionado con el riesgo de adquirir infecciones de transmisión sexual en trabajadoras sexuales de ciudades del Ecuador (11).…”
unclassified